Implementación de un sistema CNC elaborado con RAEE para dibujar circuitos PCB - Quiroz Olivares, Antony Elmer (2020)
At present, the poor management of Waste Electrical and Electronic Equipment (WEEE) puts the environment and the health of the population at risk. In 2018, more than 50 million tons of WEEE were generated worldwide. Electronic waste is more dangerous than plastic waste, as much of it is composed of various toxic elements. In this sense, this research aims to develop a system of Computerized Numerical Control (CNC) from resources composed of WEEE for the drawing of Printed Circuit Board (PCB). By taking advantage of some electronic elements and devices that make up the WEEE, it is proposed to give them a new use, preventing them from becoming waste. Once the proposed system was implemented, a CNC machine was obtained for PCB made of materials collected from WEEE, which makes drawings whose dimensions reach a maximum area of 10.